Sistem Informasi Kaji Cepat Bencana Kebakaran Bpbd Provinsi Dki Jakarta Menggunakan Java Netbeans - Firman Anggoro; Dian Nazelliana; Nia Damayanti (Universitas Muhammadiyah Riau, 2021)
The information system for rapid assessment of the BPBD of DKI Jakarta Province was built so that the fire disaster data processing system at the BPBD of DKI Jakarta Province could run precisely, effectively and efficiently. The case approach at BPBD DKI Jakarta Province uses a descriptive method, which is a method with the aim of making a systematic, factual, and accurate description of the facts and characteristics of a particular research object. In the first stage, the writer collects the data and materials needed first, and in the next stage the writer processes and discusses to arrive at a conclusion. The fire rapid assessment information system built by the author uses the Java programming language and Mysql database which can provide previous convenience in terms of processing fire data quickly and precisely compared to systems that still use manual systems, providing automatic calculations that make it easier to meet the basic needs of fire victims, and also able to generate reports of fire events, disaster reports, refugee data, calculation of basic needs and handling of fire data. Before the new system is implemented, it is recommended that the Emergency and Logistics Division be given a good explanation first, regarding the work process that will be implemented so that no incident occurs. And it is necessary to conduct training on the use of the system for the distribution section of this system so that they can know and understand how the new system works. Keywords: system, rapid assessment, fire, disaster, reporting